Levetiracetam is a useful alternative to phenytoin for epileptic seizures in children. (11th November 2019) - Cook, Rob; Davidson, Peter; Martin, Rosie
The study: Lyttle MD, Rainford NEA, Gamble C, et al. Levetiracetam versus phenytoin for second-line treatment of paediatric convulsive status epilepticus (EcLiPSE): a multicentre, open-label, randomised trial. Lancet 2019;393:2125-34. This trial was funded by the NIHR Health Technology Assessment Programme (project number 12/127/134). To read the full NIHR Signal, go to https://discover.dc.nihr.ac.uk/content/signal-000790/levetiracetam-vs-phenytoin-in-stopping-childrens-prolonged-epileptic-seizures